E-Module by Flip PDF Professional Based on Problem Based Learning (PBL) Integrated Local Wisdom to improve students’ Problem Solving Ability - Syarful Annam; Muh. Makhrus; Jamaluddin Jamaluddin; Agus Ramdani; Gunawan Gunawan (Journal of Science and Science Education, 2023)
This research aims to improve problem solving skills through E-Modules by Flip PDF Professional based on Problem Based Learning (PBL) integrated with local wisdom. The type of research is development research. The development procedure carried out refers to the 4D model development steps, namely define, design, develop, disseminate. The E-module used in the learning was developed with the flip PDF Professional application which integrated local wisdom called peraq api from Lombok, NTB. The test subjects in this research were 27 students in 7th grade at SMPN 11 Mataram. Data on students' problem solving abilities was obtained using a description (essay) test instrument with 5 questions (pre-test and pst-test). The increase in problem solving skills is calculated using the N-gain percentage formula. The research results showed that the N-gain percentage value was 63.85% in the medium category. Based on these results, it can be concluded that learning with E-Modules by Flip PDF Professional Based on Problem Based Learning (PBL) Integrated with Local Wisdom is able to improve the problem solving abilities of students in this research